Study on the Value and Approach of Labor Education in Private Colleges and Universities - Jing, Zhanfu (Journal of Theory and Practice of Contemporary Education, 2024)
At present, under the continuous reform of the education system, the development of college education is also constantly optimizing and innovating. At the present stage, the educational goals of labor education have begun to be implemented in private colleges and universities. This paper analyzes the significance of labor education in private colleges and universities, and puts forward ways to improve the effectiveness of labor education in private colleges and universities for reference, hoping that private colleges and universities can fully reflect the value of labor education.